Convenient non-profit associative forms to develop agrobusiness in Antioquia - Acevedo González, Gabriel Antonio; Sánchez Caicedo, Yomar Javier (Cooperativismo & Desarrollo, 2021)
A limitation for the sustainability of small and medium-sized agricultural producers is the marketing system, characterized by actors with high negotiation power (buyers) and others with low power (producers). To achieve a competitive position, farmers must associate, forming non-profit associative agribusinesses with high negotiation power and sufficient solidity to be sustainable. Producers are clear on the fact thatby associating they obtain better results; however, there is great skepticism about creating new associativecompanies, and the question on which non-profit association is the most convenient for a large company isfrequently asked. To answer this question, more information is required to support the proposal that motivates this research.Methodology.A sample framework of non-profit associations from 125 Antioquia municipalities was constructed, it was also calculated a sample of 50 non-profit associations from 29 town. Finally, a profound interview was conducted with 7 high profile leaders, and various processes of participant observation were realized. Results.Arguments were obtained for and against various associative forms to develop agribusiness in different situations. Conclusions.68% of non-profit enterprises, that want to change their business form, are inclined towards cooperative, since they are considered more appropriate to develop a highly competitive capacity non-profit association. For small, homogenous groups with high investment capacity, the Agrarian Transformation Society(ATS) could be viable.
Keywords: agrobusiness; competitivity; associative form; negotiation power; sustainability